2015
DOI: 10.1124/mol.114.095695
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Melastatin-3 (TRPM3)–Induced Activation of AP-1 Requires Ca2+Ions and the Transcription Factors c-Jun, ATF2, and Ternary Complex Factor

Abstract: The steroid pregnenolone sulfate activates the transcription factor activator protein-1 (AP-1) via stimulation of transient receptor potential melastatin-3 (TRPM3) channels. Here, we show that the signaling pathway requires an influx of Ca 21 ions into the cells and a rise in the intracellular Ca 21 levels. The upregulation of AP-1 was attenuated in cells that overexpressed mitogen activated protein kinase phosphatase-1, indicating that Ca 21 ions prolong the signaling cascade via activation of mitogen activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 55 publications
5
34
0
Order By: Relevance
“…Stimulation of HEK293 cells expressing TRPM3 channels with pregnenolone sulfate increases the activity of the transcription factor AP‐1. Previous experiments showed that TRPM3 expression is essential for connecting pregnenolone sulfate stimulation with enhanced transcription of AP‐1‐responsive genes [Lesch et al, , ]. Recently, we showed that the TRPM3‐induced signaling pathway requires an influx of Ca 2+ ions into the cells and a rise in the intracellular Ca 2+ concentration [Lesch et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulation of HEK293 cells expressing TRPM3 channels with pregnenolone sulfate increases the activity of the transcription factor AP‐1. Previous experiments showed that TRPM3 expression is essential for connecting pregnenolone sulfate stimulation with enhanced transcription of AP‐1‐responsive genes [Lesch et al, , ]. Recently, we showed that the TRPM3‐induced signaling pathway requires an influx of Ca 2+ ions into the cells and a rise in the intracellular Ca 2+ concentration [Lesch et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments showed that TRPM3 expression is essential for connecting pregnenolone sulfate stimulation with enhanced transcription of AP‐1‐responsive genes [Lesch et al, , ]. Recently, we showed that the TRPM3‐induced signaling pathway requires an influx of Ca 2+ ions into the cells and a rise in the intracellular Ca 2+ concentration [Lesch et al, ]. A rise in cytosolic Ca 2+ activates calcineurin, a serine/threonine phosphatase that is regulated by Ca 2+ and calmodulin [Rusnak and Mertz, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We discovered that TRPM3 stimulation induces a intracellular signaling cascade that results in the activation of the stimulus-responsive transcription factors AP-1, c-Fos, cJun, CREB, Egr-1, and Elk-1. [1][2][3][4][5] The natural ligands for TRPM3 channels are still unknown, but several compounds have been suggested to function as TRPM3-specific agonists. In most of these studies, the influx of Ca 2C ions into the cells and the subsequent rise in the intracellular Ca 2C concentration was used as an indication of activated TRPM3 channels.…”
Section: Transient Receptor Potential M3 (Trpm3) Is a Camentioning
confidence: 99%
“…The lentiviral transfer vectors pLL.TRPM3, encoding a TRPM3-specific shRNA, has been described. 1,4 The viral particles were produced as previously described 13,14 by triple transfection of 293T/17 cells with the gag-pol-rev packaging plasmid, the env plasmid encoding VSV glycoprotein, and the transfer vector.…”
Section: Lentiviral Gene Transfermentioning
confidence: 99%